Pelatihan Literasi Digital Sebagai Pembangkit UMKM DESA JATIREJO - Tri Winarsih; Rita Nataliawati; Indah Fauziah; Saras Dewi Qomariah (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
The potential of human resources in recognizing digital literacy has not been used wisely, the lack of knowledge of online marketing and product management, the use of rice as a basic ingredient for making crackers has not been fully mastered by the people of Jatirejo Village, as well as limited packaging that requires special handling in serving. Through the Focus Group Discussion (FGD) method, In-depth Interviews, as well as field assistance, it is hoped that it will be able to add insight and understanding to the people of Jatirejo Village, who previously thought that it was enough to work in the rice fields only half-heartedly in their free time managing leftover rice as crackers, now they are more daring to innovate to market on social media. The results of community service related to digital literacy training as a MSME generator are that the Jatirejo Village community welcomes digital literacy training, the ease of making rice crackers and the affordability of raw materials for making rice crackers gives new enthusiasm in developing local products from Jatirejo Village, considering relatively affordable prices in the media social services increase the motivation of all levels of village apparatus and village communities to support the revival of MSMEs.